1984
DOI: 10.1139/v84-258
|View full text |Cite
|
Sign up to set email alerts
|

A Raman and infrared study of crystalline D-fructose, L-sorbose, and related carbohydrates. Hydrogen bonding and sweetness

Abstract: Raman and infrared spectra of polycrystalline samples of four structurally related sugars, namely D-fructose, L-sorbose, 5-deoxy-D-threo-hexulose (5-deoxy-D-fructose), and D-arabinose are reported. Three regions of the spectrum have been studied: the OH stretching region 3650–3100 cm−1, the CH stretching region 3000–2800 cm−1, and the "fingerprint" region 1600–200 cm−1. Raman spectra in the region 200–10 cm−1 have also been recorded. Bands in the OH stretching region have been correlated with the [Formula: see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
1

Year Published

1984
1984
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 28 publications
2
17
1
Order By: Relevance
“…In 2 the normal order is restored with the HO-2 group being the strongest hydrogen-bond donor and the HO-1 group the strongest hydrogen-bond acceptor. These results are in sharp contrast with the hydrogen-bonding abilities determined from the infrared and Raman spectra of 1 and 2 (22). In particular, the HO-4 group was shown to be involved in the weakest hydrogen bonds in crystalline 1 and 2, and the HO-2 group to participate in the strongest hydrogen bonds in 1.…”
Section: Mulliken Population Analysiscontrasting
confidence: 80%
“…In 2 the normal order is restored with the HO-2 group being the strongest hydrogen-bond donor and the HO-1 group the strongest hydrogen-bond acceptor. These results are in sharp contrast with the hydrogen-bonding abilities determined from the infrared and Raman spectra of 1 and 2 (22). In particular, the HO-4 group was shown to be involved in the weakest hydrogen bonds in crystalline 1 and 2, and the HO-2 group to participate in the strongest hydrogen bonds in 1.…”
Section: Mulliken Population Analysiscontrasting
confidence: 80%
“…It is clear that on increasing the concentration of water, the area of the OÀH stretching region increases, because with dilution the strength of the OÀH bond increases due to hydrogen-bond formation with water. In general, as widely reported in the literature, [30,33,43,44] at room temperature the OÀH stretching band of bulk water is composed of three main components, which could be attributed to three types of water species. The first peak at 3200 cm À1 is ascribed to the inphase vibrations of the coupled OÀH symmetric stretching mode associated with tetrahedrally coordinated water molecules, as in ice.…”
Section: Secondary or Process-ii Relaxationsupporting
confidence: 62%
“…This shift of the absorption spectra of the OHstretching band towards a higher wavenumber with increasing temperature indicates that thermal agitation decreases the extent of formation of hydrogen bonds between hydroxyl groups. Since our main interest is to see how the OH-stretching region is affected by the presence of water, we carried out the detailed analysis of the OH-stretching region at different temperatures by following the scheme given by Szarek et al [33] in the case of d-arabinose. 3.…”
mentioning
confidence: 99%
“…This model does not take into consideration the other hydroxyl groups of the molecule and does not explain the considerable difference in sweetness between Dfructose and its C-5 epimer, L-sorbose: as it exists almost exclusively as a-L-sorbopyranose 5 in solution (6), this ketose is, structurally, very closely related to P-D-fructopyranose; it is, however, nearly devoid of sweet taste. The molecular properties of the two ketoses have been compared using IR spectral data (8) and by means of theoretical calculations (9-1 l), in attempts to explain this difference of sweetness. In one of these attempts (lo), the results have suggested that the assignment of the AH-B couple in P-D-fructopyranose should be reversed, making HO-1 the hydrogen bond donor and 0 -2 the acceptor.…”
mentioning
confidence: 99%